The Outsourcing and Its Relationship with Human Resources Management - Chatzi, Konstantina (Research Papers, 2023)
Human resource management is now the backbone of any modern business. It is true that a few years ago no one imagined the importance that the functions of the human resources department would have for the overall development and progress of a business. In the year 2022 we are now talking about the mutation of the Human Resource Management Department, and we are talking about the strategic HRM.On the other hand, the economic crisis and the intense competitive environment has created the need for companies to readjust their activities and even their goals so that they can meet the ever-increasing needs of the business environment. This adjustment process is called in a word flexibility. The need for flexibility is expressed through the creation of institutions. One of these institutions is the institution of outsourcing, i.e., outsourcing.